PENDUGAAN UMUR SIMPAN MI KERING DARI TEPUNG KOMPOSIT TERIGU, KELADI, DAN UBI JALAR - Elisabeth, Dian Adi Anggraeni; Setijorini, Ludivica Endang (LPPM Universitas Terbuka, 2016)
This research aimed to investigate theshelf-life of wheat, taro, and sweet potato composite flours-based dried noodles produced by a women-farming group called“Mekar Sari” in thePelaga village, Badung District, Bali. The research was conducted fromMay until November 2014. The research onthe shelf-life wasbased on the water content changing patternsby usinga completely randomized design with four treatments of thickness of PE plastic, i.e. (a) P1=0,30 mm; (b) P2=0,32 mm; and (c) P3=0,35 mm; and (d) P4=0,40 mm. The identification of shelf-life adoptedthe acceleration method (ASLT = Accelerated Shelf Life Testing)together with the Arrhenius approach. The products were stored in various storage temperatures, i.e.,20oC, 30oC (room temperature) as a control, and40oC. The results showed that PE plastic 0,35 mm was suitable for dried noodle packaging. In room temperature, shelf-life of the dried noodle was about 46 weeks.  Penelitian ini bertujuan untuk mengetahui umur simpan mi kering dari tepung komposit terigu, keladi, dan ubijalar. Produk mi kering dihasilkan oleh kelompok wanita tani (KWT) Mekar Sari di Desa Pelaga, Kabupaten Badung, Bali. Penelitian dilaksanakan pada bulan Mei sampai November 2014. Penentuan umur simpan produk mi kering berdasarkan pola perubahan kadar air menggunakan rancangan acak lengkap dengan 4 (empat) perlakuan ketebalan plastik polietilen (PE), yaitu: (a) P1=0,30 mm; (b) P2=0,32 mm; dan (c) P3=0,35 mm; dan (d) P4=0,40 mm. Penentuan umur simpan menggunakan metode ASLT (Accelerated Shelf Life Testing) dengan pendekatan Arrhenius. Produk mi kering disimpan pada berbagai suhu penyimpanan, yaitu 20oC, 30oC (suhu ruang) sebagai kontrol, dan 40oC. Hasil menunjukkan bahwa pengemasan dalam plastik PE 0,35 mm lebih sesuai untuk penyimpanan mi kering. Pada suhu ruang, umur simpan mi kering dapat mencapai sekitar 46 minggu.